Advanced chemically modified electrodes and platforms in food analysis and monitoring - Tomac, Ivana; Adam, Vojtech; Labuda, Jan (Food chemistry, 2024)
Electrochemical sensors and electroanalytical techniques become emerging as effective and low-cost tools for rapid assessment of special parameters of the food quality. Chemically modified electrodes are developed to change properties and behaviour, particularly sensitivity and selectivity, of conventional electroanalytical sensors. Within this comprehensive review, novel trends in chemical modifiers material structure, electrodes construction and flow analysis platforms are described and evaluated. Numerous recent application examples for the detection of food specific analytes are presented in a form of table to stimulate further development in both, the basic research and commercial field.
Keywords: analýza potravin; kontaminace potravin; Electrode chemical modifier; Food analysis; Electroanalytical sensors; Flow analysis; elektrody; elektrochemické techniky; Nanomaterials; Food specific analytes monitoring; Food Contamination; Electrodes; Food Analysis; Electrochemical Techniques